Nonclinical Safety Assessment of a Long-Acting Recombinant PEGylated Factor Eight (BAY 94-9027) With a 60 kDa PEG. (July 2019) - Ivens, Inge A.; Banczyk, David; Gutberlet, Katrin; Jackman, Shawna; Vauléon, Stéphanie; Frisk, Anna-Lena
BAY 94-9027 (Jivi) is a site-specifically PEGylated human B-domain-deleted (BDD) recombinant factor VIII (FVIII), with a 60 kDa branched PEG molecule attached. The nonclinical safety of BAY 94-9027 was evaluated in a toxicology program that included 2 weeks intravenous (IV) toxicity studies in rats and rabbits, a juvenile toxicity study in rats as well as a 26-week chronic study in rats. Doses of 75, 750, or 2250 IU/kg given every other day for 2 weeks did not elicit any findings related to BAY 94-9027. Specifically, no thrombus formation or histological changes such as cellular vacuolation were seen. In the chronic toxicity study, 40, 400, and 1200 IU/kg of BAY 94-9027 given twice weekly did not induce adverse effects related to BAY 94-9027, and no tissue vacuolation was observed. There was no PEG detected in choroid plexus or other areas of the brain, cerebrospinal fluid or in spleen or kidneys. These results were supported by toxicity studies in rats and rabbits treated with PEG 60 kDa attached to the maleimide linker (PEG-60-Mal-Cys). No findings related to PEG-60-Mal-Cys were seen. These results demonstrate the safety of BAY 94-9027 for long-term use.